Functional Nano Powder International Conference 2020 Selected, peer-reviewed papers from the Functional Nanopowder International Conference 2020 (FiNder 2020), November 24, 2020, Jatinangor, Sumedang, Indonesia - Joni, I Made (Trans Tech Publications Ltd, 2021)
The Functional Nanopowder International Conference 2020 (FiNder 2020) aims to explore ideas, research progress, technology, development, and collaboration among researchers and industries in powder technology and its applications. The conference is organized by Functional Nano Powder University Center of Excellence Universitas Padjadjaran, Indonesia, and managed by JP Global Transtech. We want to express our deep gratitude for generous support from the Directorate of Research and Community Service Universitas Padjadjaran, Center of Excellence in Higher Education Science and Technology Ministry of Education and Culture of the Republic of Indonesia, and great appreciation to our sponsor Dynatech, Ltd,. This book chapter contains the selected papers presented at FiNder 2020 conference. The book covers topics such as functional materials, nanopowder manufacturing, engineering materials, and others. All articles presented in this book are subject to a peer-review process conducted by our beloved colleagues. Finally, a sincere appreciation to all participants and the committee for their supports and contributions in FiNder 2020 international conference. Thank you, Editor in Chief Prof. I Made Joni, Department of Physics, Universitas Padjadjaran, Indonesia Lithium-Ion Battery, Anode, Cathode, Nanofiber, Ammonia Removal, Phosphate, Soil Acidity, Biofertilizer, Organic Pollutant, Photocatalyst, Antimicrobial Activity, Calcium Hydroxide, Biopolymer, Biocomposite, Membrane, Film Materials Science, Mechanical Engineering, Bioscience and Medicine.
Keywords: elektronické knihy; electronic books